Philippine young rural women a case study of issues and challenges to employability - Castro, Charisma Rhea S. (2005)
This paper is written on the basis of a research done on the issue of rural unemployment of young women and the need to design relevant programs specific to them. Using a combination of survey, ethnography and case study, Castro's paper explores women's perceptions on employability based on personal characteristics, attitudes, personal knowledge and skills and educational attainment. Her research reveals that young rural women rated themselves positively on basic literacy, general and actual job knowledge but unfortunately there is a severe lack of employment in the formal sector to absorb them and apply the knowledge they acquired. Majority of the women in the study are unaware of government programs that can potentially benefit them and are also hampered by their lack of proficiency and competency in mechanical, technical and entrepreneurship skills.
Keywords: Rural unemployment -- Case studies; Rural women